(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Stylistic devices like euphemisms help the speaker to make their speech colorful and make listeners think. The article aims to illustrate the origin of euphemisms and their development stages. Moreover, it discusses some stylistic tropes that are similar to euphemism or close to it.